Agronomic performance and farmer preferences of selected bean varieties in uganda, hoima and rakai districts - Awio, Bruno (Makerere University, 2015)
Genetic resources are one of the key strategies with which farmers respond to occurring and unpredicatable weather patterns. This study was aimed at testing the performance of farmer-acceptable improved multiple stress tolerant bean varieties and assessing farmers perceptions through participatory variety selection approach in the districts of Rakai and Hoima in Uganda. The specific objectives of the study were to determine the agronomic pefromance for yield and disease reaction of the bean varieties in multi-environment trials, and to understand variety selection criteria of farmers and compare it with that used by breeders to determine where there is convergence/divergence and its implications for breeding and the selection of varieties for future participatory variety selection studies. The study was conducted with nine selected farmer groups in Hoima and Rakai district. These districts were identified to experience contrasting climatic conditions, degraded soils and declining soil fertility by the Climate Change, Agriculture and Food Security programme (CCAFS) of the Consultative Group for International Agricultural Research (CGIAR). Fifteen bean varieties bred for different traits were tested in six villages to determine their performance for yield and yield components, and reaction to diseases and in nine villages for farmer preference. Each trial was planted in split plot design with two replicates. Finlay and Wilkinson (FW), the Additive Main Effect and Multiplicative Interaction (AMMI) analysis and Genotype + Genotype interaction (GGE) biplot were used to assess G x E effects on performance for key agronomic traits of the fifteen varieties in six locations. Researchers selection index were derived from the traits measured in the trials and compared with the farmers’ preference index using spearman rank correlation. The result indicates that the six environments under evaluation could best be classified in two mega-environments based on the yield output of clean seed. Mega-environment 1 consisted of Gosola village in Rakai, and three villages in Hoima district; Butimba, Butyamba and Kyakamese village while mega-environment 2 consisted of two villages; one in Rakai; Ninzi and another in Hoima, Mpalangasi village. Varieties NABE 2 and NABE 14 performed best in one mega-environment while varieties ROBA 1 and NABE 2 were the best in the second mega-environment. Based on Finlay and Wilkinson and AMMI, varieties Masindi Yellow Long, NABE 17 and CAL 143 were the most stable while varieties ROBA 1, NABE 2 and RWR 719 were high yielding but unstable in clean seed weight. The latter varieties (viz. ROBA 1, NABE 2 and RWR 719) were also highly responsive to environment difference in number of pods and in reaction to the three diseases, namely, ALS, bean rust and CBB disease severity. The number of pods per plant and reaction to disease were the traits less influenced by genotype-by-environment interaction. A significant but negative spearman rank relationship was observed between choices of researcher and that of farmers’ for varieties. Varieties RWR 719, NABE 2, NABE 14 and ROBA 1 were the best based on researcher ranking. While Masindi Yellow Long, Farmers’ seed and NABE 17 were farmer preferred varieties. Some of the introduced varieties were as well liked as the local varieties. The exotic varieties of choice included KAT B1, KATX 69, KATX 69 and KATX 56. Early maturity, seed size and colour (KAT B1) are attributes that could have favoured the varieties selection by farmers. These findings imply that Masindi Yellow Long was the most popular variety and produced stable clean seed yield across locations. The variety however, was found highly susceptible to diseases. Thus, improvement of Masindi Yellow Long by researchers would improve food security situations in the CCAFS selected sites and in the whole of Uganda. Furthermore, strong researcher-farmer collaboration will be required in the futur for selection and development of improved varieties to ensure high likelihoods of adoption of varieties that are resilient to stresses influenced by the changing seasonal weather patterns